136 Parents' report of child restraint use among children aged 0–6 years, Shanghai and Shenzhen, China-2014. (1st September 2016) - Deng, Xiao; Sauber-Schatz, Erin K; Jin, Ye; Duan, Leilei
Abstract : Background: Road traffic injuries are the second leading cause of injury death among children in China. Around 1/3 of child road traffic injuries and deaths occurred in child passengers; however, child restraint use is low and there is no national safety seat legislation. Objectives of this study: describe ownership and use of child restraints as well as parental knowledge and attitudes in the developed cities of Shanghai and Shenzhen; analyse the barriers to child restraint ownership and use. Methods: By using stratified cluster random sampling, a total of 7, 189 parents of children aged <1–6 years, who also owned a private car, participated in a self-report survey. Descriptive and multivariate analyses were used to describe collected information and determine which variables were associated with always use of child restraints. Results: Of participating parents, 39.2% owned, 33.2% ever used, 17.1% always used, and 11.4% properly used a child restraint for their child. Only 16.3% of parents answered all six key child passenger safety questions correctly. Multivariate analysis determined that the following factors influenced always using a child restraint: child's age, parental education, family income, price of car, gender of the child's driver, frequency child travels by car, average and longest distance child travels in a week, drivers' seat belt use, and parents' knowledge on child passenger safety. The leading reasons for not owning a child restraint were lack of space, low frequency of child traveling by car, difficulty installing the child restraint, and cost. The leading reasons for not using a child restraint when one was owned were: child refusal, short traveling distance, difficulty installing or using the restraint, and no space. Conclusions: This study demonstrated low child restraint use in two major Chinese cities and barriers that will need to be addressed before child restraint ownership and use will increase.